Medium ugly as a Negotiation of Digital Beauty Standards: A Critical Discourse Analysis of TikTok Content by @Cut Febrina S - Hijrah Mirna; Fadlan Barakah; Bukhari Yusuf; Cut Lusi Chairun Nisak; Firdaus Mirza Nusuary (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2026)
This study examines the discourse of medium ugly in TikTok content created by Cut Febrina Sabatini as a form of identity negotiation and criticism of digital beauty standards. Using a qualitative approach, the research applies Norman Fairclough’s critical discourse analysis through three dimensions: text, discourse practice, and sociocultural practice. Data were collected through observation of two TikTok videos uploaded on June 25 and 27, 2025, analysis of audience comments, documentation, and an in-depth interview with the content creator. The findings show that medium ugly is constructed through informal, humorous, and reflective language that creates emotional closeness with viewers and encourages self-acceptance. At the textual level, the discourse presents beauty as relative and negotiable rather than fixed. At the level of discourse practice, the content is produced from personal experience and interpreted by audiences as both validation and labeling. At the sociocultural level, the discourse challenges narrow digital beauty standards reinforced by filters, algorithms, influencer culture, and visual comparison. However, the discourse does not entirely eliminate social pressure because it shifts value from physical appearance toward intelligence, communication skills, and personal development. The study concludes that medium ugly functions as a counter-discourse that broadens the meaning of beauty, strengthens emotional solidarity, and offers a more inclusive form of self-representation in digital spaces while still reproducing new expectations of individual self-improvement. This finding highlights the ambivalent nature of resistance within platform culture.